1970
DOI: 10.1136/bmj.3.5715.146
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Syncytial Virus Infection of the Newborn

Abstract: In an outbreak of respiratory syncytial (R.S.) virus infection in a maternity hospital the respiratory illness was of a mild nature and the virus was not found in infants without respiratory symptoms. This confirms the suggestion that R.S. virus can infect infants at a very early age. Rapid diagnosis was achieved by applying the direct fluorescent antibody technique to cells in nasal secretions. This proved to be more sensitive than culture techniques where there was delay between the onset of respiratory symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

1972
1972
1992
1992

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(17 citation statements)
references
References 8 publications
0
17
0
Order By: Relevance
“…A pathological role for immune complex formation is supported by the finding that older children with high levels of circulating antibody induced by immunization with inactivated RS virus developed more severe disease than their unvaccinated counterparts when naturally infected with RS virus (Kim et al, 1969). Nevertheless, a protective role for maternal IgG is implied by the facts that RS virus infections of the lung are rare during the first 4 weeks of life (Neligan et al, 1970) and that babies born to mothers with high levels of antibody reactive in the membrane fluorescence test were protected for several months (Ogilvie et al, 1981). Such anomalies can be explained if antibodies to the RS virion surface or the infected cell membrane protect against infection, whereas antibody to other virus components fails to protect and may even lead to immune complex reactions.…”
Section: Introductionmentioning
confidence: 55%
“…A pathological role for immune complex formation is supported by the finding that older children with high levels of circulating antibody induced by immunization with inactivated RS virus developed more severe disease than their unvaccinated counterparts when naturally infected with RS virus (Kim et al, 1969). Nevertheless, a protective role for maternal IgG is implied by the facts that RS virus infections of the lung are rare during the first 4 weeks of life (Neligan et al, 1970) and that babies born to mothers with high levels of antibody reactive in the membrane fluorescence test were protected for several months (Ogilvie et al, 1981). Such anomalies can be explained if antibodies to the RS virion surface or the infected cell membrane protect against infection, whereas antibody to other virus components fails to protect and may even lead to immune complex reactions.…”
Section: Introductionmentioning
confidence: 55%
“…Further studies have shown that RS virus may infect infants still in maternity homes but producing only mild illness (Neligan et al, 1970) and is a cause of severe illness in ward cross-infection (Ditchburn, McQuillin, Gardner & Court, 1971). The seriousness of RS virus infection is also emphasized by the deaths which it causes.…”
Section: Discussionmentioning
confidence: 99%
“…Further, bronchiolitis is relatively uncommon in the first 6 weeks of life when antibody levels are at their highest [143,158]. Though these young infants may be susceptible [139] to infection which indeed may be severe [57] or fatal [67], symptoms such as lethargy, mild respiratory symptoms [139] and apnoea [11,23,149] are more common than pneumonia or severe airways obstruction. The protective effect of high maternally acquired or passively administered antibody also mitigates against the immune complex hypothesis.…”
Section: Immunology and Possible Immunopathology The Role Of Antibmentioning
confidence: 99%